THE EFFECTS OF HIIT AND TABATA CIRCUIT TRAINING ON THE ENDURANCE OF ATHLETES AT PION MAS SCHOOL GROBOGAN SOCCER ACADEMY - Nadhif Fauzan Adi Candra; Setiyawan Setiyawan; Danang Aji Setyawan (Journal of Physical Activity and Sports (JPAS), 2026)
This study aims to analyse the effects of High-Intensity Interval Training (HIIT) and Tabata Circuit Training on the endurance of athletes at the Pion Mas Soccer School (SSB) in Grobogan Regency and to compare the effectiveness of these two training methods. The study employed a quantitative approach using an experimental method with a True Experimental design in the form of a pretest–posttest control group design. The sample consisted of 20 male athletes aged 12–15 years, divided into two groups: 10 athletes in the HIIT group and 10 athletes in the Tabata Circuit Training group. The Multistage Fitness Test (MFT) was used to measure VO?max capacity. Data analysis included normality tests, homogeneity tests, paired-sample t-tests, and independent-sample t-tests. The results showed that both training methods had a significant effect on improving the athletes’ endurance (p < 0.05). The HIIT group showed a greater increase in VO?max compared to the Tabata Circuit Training group. However, the results of the independent-samples t-test showed no significant difference between the two methods (p = 0.058). Thus, both HIIT and Tabata Circuit Training are equally effective in improving the endurance of soccer players.